(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The Office of State Wealth Services and Auction is one vertical agency of the Directorate General of State Assets responsible to the DJKN Lampung and Bengkulu Regional Offices,The Office of State Wealth Services and Metro Auction operates two functions. First, The Office of State Wealth Services and Metro Auction run function as the executor of regional level State Property Management and the second function as the Property User Authority in its position as a vertical office within the Ministry of Finance.The method used in this research is Enterprise Architecture Planning. While the data collection methods used are interviews, observation and literature study. The analysis process begins with the planning stages, understanding the current conditions, then making an enterprise architecture model using Enterprise Architecture Planning,the next step is making the implementation plan and application portfolio and the process of testing the enterprise architecture model which includes data architecture, information architecture, application architecture, technology architecture.This research results in a blueprint for the design of Enterprise Architecture Planning (EAP) and the upcoming Asset Management Information System Development utilizing Mobile-based technology in managing asset management both operationally and financially and ensuring that the assets are managed, controlled and used efficiently and effectively.